2014
DOI: 10.1016/j.cub.2014.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-Va and Dynamic Actin Oppose Microtubules to Drive Long-Range Organelle Transport

Abstract: SummaryIn animal cells, microtubule and actin tracks and their associated motors (dynein, kinesin, and myosin) are thought to regulate long- and short-range transport, respectively [1–8]. Consistent with this, microtubules extend from the perinuclear centrosome to the plasma membrane and allow bidirectional cargo transport over long distances (>1 μm). In contrast, actin often comprises a complex network of short randomly oriented filaments, suggesting that myosin motors move cargo short distances. These observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 36 publications
5
65
0
2
Order By: Relevance
“…It is reported for melanocytes that both kinesin and myosin Va are involved in the transportation and secretion of melanosomes 5052 . Identification of myosin motors responsible for Col-1 secretion requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported for melanocytes that both kinesin and myosin Va are involved in the transportation and secretion of melanosomes 5052 . Identification of myosin motors responsible for Col-1 secretion requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…MyoVa function, on the other hand, was indispensable for the peripheral distribution of melanosomes on the actin network (5-7, 28, 29). Depolymerization of the actin network or the absence of MyoVa resulted in a microtubule-dependent clustering of melanosomes in the cell center (28,30,31). However, the signaling pathway(s) that regulate the directionality of the melanosome transport on the microtubule and actin networks have not yet been delineated.…”
Section: Significancementioning
confidence: 99%
“…Evans et al. indicated that MyosinVa (MyoVa) and actin are another main drivers of melanosome dispersion in murine melanocytes …”
Section: Introductionmentioning
confidence: 99%